Political economy of conflict and violence against women: cases from the South - Samuel, Kumudini; Slatter, Claire; Gunasekara, Vagisha (Zed, 2019)
The Political Economy of Conflict and Violence against Women shows how political, economic, social and ideological processes intersect to shape conflict related gender-based violence against women. Through feminist interrogations of the politics of economies, struggles for political power and the gender order, this collection reveals how sexual orders and regimes are linked to spaces of production. Crucially it argues that these spaces are themselves firmly anchored in overlapping patriarchies which are sustained and reproduced during and after war through violence that is physical as well as structural. Through an analysis of legal regimes and structures of social arrangements, this book frames militarization as a political economic dynamic, developing a radical critique of liberal peace building and peace making that does not challenge patriarchy, or modes of production and accumulation.